2022
DOI: 10.1126/sciadv.abo5555
|View full text |Cite
|
Sign up to set email alerts
|

TSC22D4 interacts with Akt1 to regulate glucose metabolism

Abstract: Maladaptive insulin signaling is a key feature in the pathogenesis of severe metabolic disorders, including obesity and diabetes. Enhancing insulin sensitivity represents a major goal in the treatment of patients affected by diabetes. Here, we identify transforming growth factor–β1 stimulated clone 22 D4 (TSC22D4) as a novel interaction partner for protein kinase B/Akt1, a critical mediator of insulin/phosphatidylinositol 3-kinase signaling pathway. While energy deprivation and oxidative stress promote the TSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…In cSCC (Figure 3C and Table S7), a relatively consistent trend for an upregulation of cluster unique genes that enhancing NK cell activation or expansion were detected in C0 (CD2, CD52) 61,62 , C1 (NCR3, OASL, NFKBIZ, TSC22D4) 63,64 , C2 (KLRC3, IKZF3, ETS1, NFIL3, JAK1, NKTR) 65,66 , and C4 (GNLY, TNFSF10) 67 , and a downregulation of immunosuppressive genes were concertedly detected in C0 (USP14) 68 , C1 (TNFRSF18, HLA-B, HLA-C) 6971 , and C4 (IKZF2, LAG3, KIR2DL1) 30 , consistent with the elevated NK cell activation signatures in all NK cell clusters from the tumor of SCC. (Figure 2D).…”
Section: Resultsmentioning
confidence: 75%
“…In cSCC (Figure 3C and Table S7), a relatively consistent trend for an upregulation of cluster unique genes that enhancing NK cell activation or expansion were detected in C0 (CD2, CD52) 61,62 , C1 (NCR3, OASL, NFKBIZ, TSC22D4) 63,64 , C2 (KLRC3, IKZF3, ETS1, NFIL3, JAK1, NKTR) 65,66 , and C4 (GNLY, TNFSF10) 67 , and a downregulation of immunosuppressive genes were concertedly detected in C0 (USP14) 68 , C1 (TNFRSF18, HLA-B, HLA-C) 6971 , and C4 (IKZF2, LAG3, KIR2DL1) 30 , consistent with the elevated NK cell activation signatures in all NK cell clusters from the tumor of SCC. (Figure 2D).…”
Section: Resultsmentioning
confidence: 75%
“…Consistently, the activation of ApoM/S1P complex, which also activates the AKT pathway, can prevent IR progression through upregulating SIRT1 75 . More recently, it was shown that TGFβ1 stimulated clone 22 D4 (TSC22D4) is a novel interaction partner for AKT, and its dysregulation is able to disrupt insulin sensitivity and glucose disposal in mice 76 …”
Section: Signaling Pathways In T2dmmentioning
confidence: 87%
“…75 More recently, it was shown that TGFβ1 stimulated clone 22 D4 (TSC22D4) is a novel interaction partner for AKT, and its dysregulation is able to disrupt insulin sensitivity and glucose disposal in mice. 76 It is well known that lipid metabolism and chronic inflammation could modulate AKT-associated insulin sensitivity and IR. Diacylglycerol accumulation in the liver impairs the AKT activity through PKC, [77][78][79][80] an inhibitor of the PI3K/AKT2 pathway.…”
Section: Pi3k/akt Pathwaymentioning
confidence: 99%
“…The state of insulin resistance is a precursor and concomitant state of T2D(Petersen & Shulman, 2018) characterized by disrupted insulin receptor (InsR) signalling (Nagarajan et al, 2016). The IR β /PI3K/AKT signalling pathway plays an important role in insulin signalling, induction of glucose uptake and regulation of cell metabolism, growth and differentiation (Demir et al, 2022; Taniguchi et al, 2006). The IR β /PI3K/AKT pathway was highly expressed in homogenates of db/db mouse kidneys and HUVECs treated with high glucose.…”
Section: Discussionmentioning
confidence: 99%